60 Neoadjuvant Imatinib Mesylate – an Ace of Spaces for Surgical Management of an Oesophago-Gastric Junction Gastro-Intestinal Stromal Tumour. (28th February 2022) - Arora, A.; Arkle, T.; Sreedharan, L.; Kumar, B.
Abstract: Introduction: Oesophageal gastro-intestinal stromal tumours (GISTs) are rare, accounting for less than five percent of all GIST, with the majority of these occurring at the oesophago-gastric junction (OGJ). Due to the anatomical location and size of these tumours at presentation, surgical resection is often a major undertaking. Neoadjuvant treatment with tyrosine kinase inhibitors, such as Imatinib mesylate, have the potential to downstage such tumours, thereby limiting the extent of subsequent surgical resection. This may therefore reduce any potentially associated morbidity and mortality. Case Description: We report the case of a 75-year-old gentleman who presented with a large OGJ GIST, which presented with dysphagia. The tumour was deemed too large for local excision due to the risk of compromising the lumen at the OGJ in attempting to obtain a clear resection margin. Given the patient's co-morbidity, oesophagectomy or total gastrectomy was deemed too major an undertaking. Therefore, endoscopic biopsies were obtained with a view to possible neoadjuvant therapy. These confirmed DOG-1 and Exon-11 mutations, suggesting sensitivity to Imatinib mesylate. A standard dose regime of 400mg daily for a planned 36-month course was commenced. Subsequent imaging showed a substantial decrease in tumour bulk and the decision was made to perform a local excision. A local enucleation procedure was performed, and the patient made a sound recovery. Post-operative histology of resected tumour showed almost complete tumour regression. Discussion: This significant response to neoadjuvant Imatinib mesylate therapy demonstrates clear potential for its use in similar cases, where radical resection would cause significant morbidity and risk mortality.